2023
DOI: 10.1055/s-0043-1762585
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Links between Nonalcoholic Fatty Liver Disease and Neurodegeneration

Abstract: The association between liver and brain health has gained attention as biomarkers of liver function have been revealed to predict neurodegeneration. The liver is a central regulator in metabolic homeostasis. However, in nonalcoholic fatty liver disease (NAFLD), homeostasis is disrupted which can result in extrahepatic organ pathologies. Emerging literature provides insight into the mechanisms behind the liver–brain health axis. These include the increased production of liver-derived factors that promote insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…Research findings have indicated that MASLD exhibits a correlation with an elevated susceptibility to cerebrovascular complications [9,119]. This association subsequently contributes to the occurrence of neurodegenerative alterations within the brain and an augmented likelihood of developing dementia [120,121]. Critical to physiological nitric oxide (NO) production is endothelial nitric oxide synthase (eNOS), an enzyme that is primarily found in the endothelium of blood vessels [122].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Research findings have indicated that MASLD exhibits a correlation with an elevated susceptibility to cerebrovascular complications [9,119]. This association subsequently contributes to the occurrence of neurodegenerative alterations within the brain and an augmented likelihood of developing dementia [120,121]. Critical to physiological nitric oxide (NO) production is endothelial nitric oxide synthase (eNOS), an enzyme that is primarily found in the endothelium of blood vessels [122].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Hepatic encephalopathy, the presence of comorbid psychoses in patients with advanced liver diseases, is associated with pathological inflammation, microglial activation, and metabolic imbalances (Butterworth 2013 ). Similarly, nonalcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) promote degenerative neuroinflammation (Kelty et al 2023 ).…”
Section: The Liver-brain Axismentioning
confidence: 99%